Pengembangan Bahan Ajar Buku Teks IPS Tema Indahnya Kebersamaan Pada Peserta Didik Kelas 4 MI An Nuriyah Kwanyar Bangkalan - Faqih, Nurul Makrifah; Fauzi, Nur (LPPM, 2020)
This research aims to develop Social Science Textbook teaching materials. The material teaching is developed in the form of social studies textbooks with the theme